Novel ubiquitin-independent nucleolar c-Myc degradation pathway mediated by antizyme 2 - Murai, Noriyuki (Sci Rep, 2018)
The proto-oncogene c-Myc encodes a short-lived protein c-Myc that regulates various cellular processes including cell growth, differentiation and apoptosis. Degradation of c-Myc is catalyzed by the proteasome and requires phosphorylation of Thr-58 for ubiquitination by E3 ubiquitin ligase, Fbxw7/ FBW7. Here we show that a polyamine regulatory protein, antizyme 2 (AZ2), interacts with c-Myc in the nucleus and nucleolus, to accelerate proteasome-mediated c-Myc degradation without ubiquitination or Thr-58 phosphorylation. Polyamines, the inducer of AZ2, also destabilize c-Myc in an AZ2-dependent manner. Knockdown of AZ2 by small interfering RNA (siRNA) increases nucleolar c-Myc and also cellular pre-rRNA whose synthesis is promoted by c-Myc. AZ2-dependent c-Myc degradation likely operates under specific conditions such as glucose deprivation or hypoxia. These findings reveal the targeting mechanism for nucleolar ubiquitin-independent c-Myc degradation.